Applications.Communication for personal and professional contexts - Payne, James (Clark Publishing, 2001)
This text proceeds from the idea that you want to improve your communication. More than that, it is built on the idea that when you improve your own communication, you will improve your life ...personally and professionally. By practicing responsible communication, you will meet your own needs while ben-efiting others. We cannot live our lives taking our communication for granted. It is far too important to forget about. Like eating and breathing, it keeps us alive.